Ecology of impala (Aepyceros melampus) and waterbuck (Kobus ellipsiprymnus) in Majete Wildlife Reserve, Malawi - Spies, Karherine Sarah (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScConsEcol)--Stellenbosch University, 2015.